MECHANISM OF INDICTMENT. PROBLEMS, THEORY AND PRACTICE - T. A. Gumerov (Russian Journal of Economics and Law, 2017)
Objective: to determine the stages of the mechanism of pre-trial adoption of indictment, to identify the main mistakes made when making an indictment, and offer ways of their elimination.Methods: logical, comparative-legal, normative-logical and statistical, as well as the method of complex study of phenomena and processes of legal reality.Results: within the framework of the proposed mechanism of pre-judicial indictment adoption, and basing on the analysis of 45 indictments and their receipts in various categories of cases, the common errors were identified of the subjects of criminal procedural law involved in the mechanism of indictment preparation and adoption. These include: the presence of smudges, underlined places and erasures in the text of the indictment; the discrepancy between the indictment and the charges set out in the resolution on impleading of a defendant; confusion referred to the approval of the indictment by the head of the investigative body, etc. Therefore, it is proposed to supplement Part 1 of Article 39 of the Russian Criminal-Procedural Code with paragraph 9.1. "To agree on the indictment after its signing by the investigator", to extend the term of preliminary investigation and to assign additional days for the indictment approval, to put into practice the meeting of all actors of the criminal process involved in the mechanism of the indictment adoption, in order to analyze the quality and completeness of the investigation, typical investigation errors and violations of criminal-procedural legislation.Scientific novelty: as a result of the study, frequent errors arising from the adoption of the indictment were identified, occurring since the end of the preliminary investigation with indictment till the adoption of the criminal case with the indictment by the court; suggestions on avoiding them were formulated.Practical significance: the main provisions and conclusions of the article can be used in scientific and teaching activities, in addressing the issues related to the mechanism of the indictment preparation and adoption.